Phương trình chứa căn

Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Trần Mạnh Tiến

rut gon P=\(\frac{a-1}{\sqrt{b-1}}\sqrt{\frac{b-2\sqrt{b}+1}{a^2-2a+1}}\) voi a<1;b>1

Hiệu diệu phương
5 tháng 8 2019 lúc 11:23

P=\(\frac{a-1}{\sqrt{b-1}}\sqrt{\frac{b-2\sqrt{b}+1}{a^2-2a+1}}=\frac{a-1}{\sqrt{b-1}}\sqrt{\frac{\left(\sqrt{b}-1\right)^2}{\left(a-1\right)^2}}=\frac{a-1}{\sqrt{b-1}}.(\frac{\sqrt{b}-1}{a-1})=\frac{\sqrt{b}-1}{\sqrt{b-1}}\)


Các câu hỏi tương tự
Darkn256
Xem chi tiết
Tớ Thích Cậu
Xem chi tiết
Thiều Khánh Vi
Xem chi tiết
Anh Tú Dương
Xem chi tiết
Trần Mạnh Tiến
Xem chi tiết
Trần Mạnh Tiến
Xem chi tiết
Nguyễn Thế Mãnh
Xem chi tiết
Lê Thụy Sĩ
Xem chi tiết
Nguyễn Ngọc Trâm
Xem chi tiết